Olanzapine-induced metabolic syndrome is partially mediated by oxytocinergic system dysfunction in female Sprague-Dawley rats - Elsie D. Oduor; Peter W. Mwangi; Boniface M. Chege; Sharon F. Olago; Frederick Bukachi (PLoS ONE, 2025)
Introduction Olanzapine (OLZ), a second-generation antipsychotic, is associated with the development of metabolic syndrome with unclear underlying pathophysiologic mechanisms. Oxytocin (OT) influences feeding, lipid, and glucose metabolism. This study investigates whether dysfunction in the oxytocinergic system contributes to the development of olanzapine-induced metabolic syndrome. Methods Twenty five (25) female Sprague-Dawley rats were housed under standard conditions and studied over 12 weeks. During the first 6-week induction phase, rats were randomized into 3 groups: normal control (vehicle treatment; normal saline; n = 5), low dose (4 mg/kg olanzapine [OLZ]; n = 5), and high dose (8 mg/kg OLZ; n = 15). In the last 6-week treatment phase, the high dose group was re-randomized into 3 groups: negative control (8 mg/kg OLZ; n = 5), positive control (8 mg/kg OLZ + 500 mg/kg metformin; n = 5), and test group (8 mg/kg OLZ + 1 mg/kg oxytocin [OT]; n = 5). The normal control and low dose groups continued unchanged. Body weight, food intake, glucose levels, OGTT, lipid profile, visceral fat, hepatic index, hepatic triglycerides, and steatosis were assessed. Results At induction end, high-dose OLZ increased food intake (179 ± 5 g), body weight (239 ± 3 g), blood glucose (7.8 ± 0.3 mmol/L), and impaired glucose tolerance (846 ± 25 mmol/L·min) compared to controls (p < 0.0001). Post-treatment, the test group displayed reduced food intake (163 ± 2 g vs. 197 ± 6 g), body weight (297 ± 2 g vs. 376 ± 6 g), blood glucose (5.8 ± 0.3 mmol/L vs. 9.8 ± 0.2 mmol/L), and improved glucose tolerance (711 ± 14 vs. 853 ± 9 mmol/L·min) compared to negative controls (p < 0.0001). LDL-C, total cholesterol, serum and hepatic triglycerides, visceral adipose, and hepatic mass and steatosis were also significantly decreased in the test group compared to negative control group (p < 0.01). Conclusion OLZ-induced metabolic abnormalities were mitigated by oxytocin, indicating that the oxytocinergic system hypofunction may be implicated in its pathophysiology. These results highlight OT’s therapeutic potential and call for further clinical research to explore its role in the management of antipsychotic-induced metabolic syndrome.